Time of Enterotoxin Formation and Release During Sporulation of Clostridium perfringens Type A - Duncan, Charles L. (1973)
Clostridium perfringens enterotoxin was detected intracellularly about 3 hr after the inoculation of vegetative cells into sporulation medium. The subsequent increase in intracellular enterotoxin concentration roughly paralleled but followed by 2.5 to 5 hr the increase in number of heat-resistant spores. The increase in biologically active toxin coincided with the increase in enterotoxin antigen. Enterotoxin was released from the sporangium with its lysis, concomitantly with the mature spore release.